The Educational Role of the Physical Education Teacher in Identifying and Addressing the Phenomenon of School Violence Among Primary School Students - Ghyaidh, Hussein Rashid (Indonesian Journal Publisher, 2025)
The research aims to understand the educational role of the physical education teacher in identifying differences in the average scores of school violence and the theoretical average of the scale, as well as identifying differences in the average of school violence according to the variable of type of violence (physical - verbal), and identifying differences in the average of school violence according to the variable of gender (male - female students). The researcher used the descriptive approach using the survey method. To achieve this, the researcher used the questionnaire as a tool to collect data and information from a random sample of (20%) of the research community, which numbered (750) male and female physical education teachers in the Diwaniyah Education Directorate, who were regularly attending the official school year (2022-2023). Accordingly, the sample size reached (150) male and female physical education teachers, with (100) male teachers, which constitutes (67%) of the research sample, compared to (50) female teachers, which constitutes (33%) of the research sample. Appropriate statistical methods were used for the current research, and the research results showed the presence of school violence among primary school students, as it came with a larger arithmetic mean. From the theoretical mean of the scale used to measure it, the percentage of physical school violence was generally higher than that of verbal school violence among elementary school students. The average level of school violence among male students was higher than the average level of school violence among female students, meaning that male students were more violent than female students.